(untitled) (Innovation in Woodworking Industry and Engineering design, 2013)
A study on the technologies for creating and growing SRC plantations for the production of biomass for energy purposes has been conducted in the present report. An analysis of the main steps in the technological process has been made. Recommendations are made to the Bulgarian farmers on the necessary techniques for incorporating the crops and the use of appropriate machinery for site preparation, planting and growing of crops.